[MEMORANDUM TO THE MEMBERS OF THE EXECUTIVE COMMITTEE - CHILCOTE, SAMUEL (Tufts Archival Research Center, 2007)
Confidential; Memorandum from Sam Chilcote to the executive committee regarding health care reform and excise tax increases. Reports that states with high percentage of farming would be very negatively effected by an increased tobacco tax. Justifies targeting of youth by stating that the industry has the right to market its product. Adds that health care should not be funded by a cigarette tax.